Prevalence of Ototoxic Medication Use among Older Adults in Beaver Dam, Wisconsin - Joo, Yoonmee (J Am Assoc Nurse Pract, 2018)
BACKGROUND AND PURPOSE: Drug-related ototoxicity may exacerbate presbycusis (age-related hearing loss), yet few data are available on the prevalence of ototoxic medication use by older adults. The purposes of this study were to assess the impact of aging and ototoxicity on hearing loss, the prevalence of ototoxic medication use and, select characteristics associated with ototoxic medication use among older adults. METHODS: Cross-sectional analyses were conducted using select variables extracted from the baseline and 10-year follow-up assessments of the two population-based epidemiological studies to compare two points in time. RESULTS: Ninety-one percent of the sample was taking a medication reported to be ototoxic. Non-steroidal anti-inflammatory drugs were the most commonly used (75.2%), followed by acetaminophen (39.9%) and diuretics (35.6%). Hypertension, diabetes, cardiovascular disease, and history of smoking were associated with ototoxic medication use. Participants with hearing loss were taking a significantly greater number of ototoxic medications than those without hearing loss. CONCLUSION: Known ototoxic medications are widely used. Any subsequent ototoxicity may interact with age changes and a more severe hearing loss than that associated with age alone. IMPLICATIONS FOR PRACTICE: Nurse practitioners should inform older adults about the possibility of drug-related ototoxicity and monitor hearing acuity of all older adults taking known ototoxic medications.